The potential of miRNA-based therapeutics in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection: A review - Leonny Dwi Rizkita; Indwiani Astuti (Elsevier, 2021)
Since the World Health Organization (WHO) declared COVID-19, the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as a pandemic in March 2020, and more than 117 million people worldwide have been confirmed to have been infected. Scientists, medical professionals, and other stakeholders are racing against time to find and develop effective medicines for COVID-19. However, no drug with high efficacy to treat SARS-CoV-2 infection has been approved. With the increasing popularity of gene therapy, scientists have explored the utilization of small RNAs such as microRNAs (miRNAs) as therapeutics. miRNAs are non-coding RNAs with high affinity for the 3'-UTRs of targeted messenger RNAs (mRNAs). Interactions between host cells and viral genomes may induce the upregulation or downregulation of various miRNAs. Therefore, understanding the expression patterns of these miRNAs and their functions will provide insights into potential miRNA-based therapies. This review systematically summarizes the potential targets of miRNA-based therapies for SARS-CoV-2 infection and examines the viability of possible transfection methods.